Actualización terapéutica de la gonartrosis en adultos mayores - Chafla Quishpi, Byron Alexander (2023)
ABSTRACT: Gonarthrosis is defined as a disease characterized by the progressive and irreversible loss of articular cartilage, bone remodeling and varying degrees of inflammation in the form of synovitis; is a disease that occurs mainly in older adults where it is diagnosed in up to 80% of elder adults. The aim of this research was to update the related knowledge with therapeutic management in elders with gonarthrosis. A basic, non-experimental, descriptive research is carried out and a cross-sectional cohort consisting of a non-systematic literature review. The main results include the need to implement non-pharmacological treatment as the essence of initial interventions for osteoarthritis of knee, but as a next step there is pharmacological intervention, which has focused on the control or reduction of pain in addition to improving the functional capacity of the joints. In addition, intra-articular therapeutics have obtained promising results in rigorous trials, acquiring advantages such as greater bioavailability, maintaining a better safety profile, affordable costs, less systemic exposure and few adverse effects. It is concluded that the appropriate treatment for knee osteoarthritis in older adults consists of starting with non-pharmacological management such as physical rehabilitation, diet, physical exercise, especially aerobic exercise, subsequently it is possible to begin pharmacological therapy with oral NSAIDs or acetaminophen, consequently. Intra-articular injections are an option in the non-surgical management of back pain due to their good safety profile with minimal side effects. On the other hand, if conservative treatment is ineffective and pain persists, surgical intervention, ideal for older adults, such as arthroscopy and knee arthroplasty, is required